Synthesis and characterization of indium-doped ZnO nanoparticles by coprecipitation method for highly photo-responsive UV light sensors - Yogesh B. Waghadkar; Govind Umarji; Shankar S. Kekade; Sunit Rane; Ratna chauhan; Muthupandian Ashokkumar; Suresh W. Gosavi (Sensors International)
In this investigation, we employed a cost-efficient co-precipitation technique to synthesize nanostructures of Indium-doped ZnO, incorporating varying percentages of Indium (0.25 %, 0.5 %, 1 %, 2 %, and 4 %) into the ZnO lattice. These Indium atoms were introduced either by replacing oxygen (O2) or occupying tetrahedral interstitial spaces within the structure. The resultant materials exhibited an average crystal size ranging from approximately 5 to 10 nm and displayed a highly crystalline nature. The UV–visible spectroscopy of these synthesized materials, revealing an excitation spectrum spanning 380 nm–395 nm. Photoluminescence measurements showed two distinct emission peaks at 390 nm and 471 nm, originates from the recombination of the free excitons through an exciton-exciton collision process and the presence of defects or impurities in the In–ZnO nanostructures. Defects in the crystal lattice, such as oxygen vacancies or interstitial defects, can create energy levels within the bandgap. Subsequently, we evaluated the suitability of these Indium-doped ZnO nanostructures for light sensor applications. Response and recovery times to infrared (IR), visible, and ultraviolet (UV) light was recorded. Remarkably, the nanostructures exhibited exceptional response and recovery times, in UV light compared to their performance with IR and visible light. This significant performance of synthesized materials in UV light shows the cost-effective co-precipitation method in fabricating Indium-doped ZnO nanostructures for UV light sensing applications.